Pengaruh profitabilitas dan leverage terhadap harga saham pada perusahaan teknologi informasi dan komunikasi di Bursa Efek Indonesia Periode Pra- Covid dan Pasca Covid (2019-2024) - Beatrice Phoebe Gantari Manusu; Diana Zuhroh (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
This study examines the influence of profitability and leverage on stock prices of Technology, Information, and Communication (TIK) sector companies listed on the Indonesia Stock Exchange (IDX) during the pre-pandemic period (2019–2021) and the post-pandemic period (2022–2024). Profitability is measured using Return on Equity (ROE), while leverage is measured using the Debt to Equity Ratio (DER). A quantitative approach with multiple linear regression is applied to 114 observations from 19 companies with complete financial data across both periods. The results of the study indicate that ROE has a positive and significant effect on stock prices in both periods, reaffirming that profitability is a key indicator considered by investors in the ICT sector. Conversely, DER does not exhibit a significant effect on stock prices in either period, suggesting that leverage levels are not a primary consideration for investors when making investment decisions, regardless of whether market conditions are depressed or have returned to stability. Simultaneously, ROE and DER jointly influence stock prices, implying that companies need to strengthen their profitability and maintain healthy leverage in order to preserve firm value.